Pengaruh Jenjang Pendidikan dan Pelatihan Kerja terhadap Produktivitas Kerja Pegawai Kantor Kementerian Agama Kabupaten Pasuruan - Ainun Jariyah; Pompong Budi Setiadi; Sri Rahayu (Journal on Education, 2023)
Work productivity is an essential factor in completing a job and achieving organizational goals. The ability of human resources, both soft skills and hard skills, is an essential factor that affects one's work productivity. In his study, work productivity was influenced by both external and internal factors which included education level, skills, discipline, attitude, work ethic, motivation, nutrition and health, income level, social security, work environment, work climate, technology, production facilities, management, and performance. This study aims to analyze the influence of the level of education and job training factors on the work productivity of employees at the Office of the Ministry of Religion, Pasuruan Regency. The urgency of the gap in the selection of education and training level variables is because education is a means of developing critical thinking and is very important in applying the use of logic when making decisions and interacting with others. Meanwhile, training is a means of learning to increase productivity and performance by equipping employees with the skills they need to complete important tasks. The method used in this study is quantitative with multiple linear regression tests. The research data or sample is 50 respondents. The research instrument used to obtain data is by using a questionnaire. The results of the study found that the level of education had no effect on work productivity. Meanwhile, job training has a significant effect on work productivity. In the simultaneous test, both education and training simultaneously have an influence on work productivity variables